Identificación y biocontrol de los microorganismos causantes de la Marchitez Vascular del Babaco (Vasconcellea heilbornii Badillo) procedentes de Loja. - Correa Jiménez, Auliria Francisca (2024)
Babaco vascular wilt disease (BVD), caused by a complex of fungi of the genus Fusarium spp. is one of the most economically important diseases. It has caused great devastation in the crop's plantations, leading growers to use chemical control strategies and even to stop the activity due to the decrease in yields. There is a useful and environmentally friendly control alternative: biological control, which proposes the search for antagonistic microorganisms to control pathogenic microorganisms. The objective of this research was first to characterize the isolates associated with BVM in Loja, for which samples of Babaco roots with symptoms of BVM were collected and characterized morphologically and culturally, taking into account aspects such as: colony pigmentation, mycelial type, measurement of radial growth, spore count, measurement of macro and microconidia. Posteriorly, the in vitro antagonism of Trichoderma spp. Penicillum spp. and Lecanicillum spp. against the 5 isolates of Fusarium spp. was evaluated using a completely randomized design with bifactorial arrangement and the data were statistically processed by testing assumptions of homogeneity and variance by Tukey's tests. The results obtained indicate that the 5 isolates present characteristics corresponding to the genus Fusarium spp. in which variability was observed, reflecting the presence of various species of Fusarium spp. and according to the radial growth rate, two classification categories were identified: 2 isolates with medium growth and 3 with rapid growth. Regarding biocontrol, the results indicate that the strain of Trichoderma spp. showed a high potential of PICR: >50 % of the isolates of Fusarium spp, so it is classified as a good controller. Penicillum spp. and Lecanicillum spp. strains showed a lower potential as biocontrollers. It is concluded that Trichoderma spp. is the best controller, standing out for its efficacy in the inhibition of Fusarium spp.